Tipificación de tres marcadores genéticos de caracteres de importancia comercial en ganado Charolais: implicaciones en la ganadería para carne en México - Parra Bracamonte, Gaspar Manuel; Sifuentes Rincón, Ana M.; Arellano Vera, Williams; Almanza González, Alberto; De la Rosa Reyna, Xochitl F. (Revista Colombiana de Ciencias Pecuarias, 2009)
Summary Samples from registered Charolais sire candidate bulls for breeding herds and managed in a performance test station (N=130) were analyzed in order to estimate genotypic and allelic frequencies of three single nucleotide polymorphisms associated to beef quality traits. Two Calpain gene SNP markers, CAPN316 and CAPN4751, and the Charolais private mutation Q204X associated to double-muscling phenotype, were assessed. High frequency of normal allele was observed in CAPN316 (f=0.85) and similar frequencies for normal and favorable alleles in CAPN4751 (f=0.58 and 0.42, respectively). For Q204X, a low prevalence for the double muscling promoter allele was observed (f=0.03) attributable to negative selection criterion over this trait in the last 30 years. Implication and validation effects of the marker effects on the beef production system are discussed. Implementation of marker assisted management could help system development, support creation of quality meat niches and facilitate the increasing profitability for current beef production industry.